Solução de problemas e mapas conceituais: um estudo de aplicação de software na aprendizagem de ecologia - Oliveira, Marlos Joaquim de (2017)
This research aims to analyze the production of conceptual maps in the construction of concepts and problem solving in ecology classes. From the application of a mini-course on water resources in the urban environment, in the High School, in the city of Caldas Novas, it was verified that the foundations of significant learning by discovery using conceptual maps and solving problems with Cmap Tools software technology are very important in class. For the teaching methodology, we opted for the application of conceptual maps, field work and the resolution of a poorly structured problem. As a data collection tool, three instruments were selected to be qualitatively evaluated in 16 students of a private school, by specific rubrics whose data, after collection, were tabulated and made available as graphs. Simultaneously with the adoption of the methodology of conducting the mini-course, we adopted unstructured observation, which objectively sought to evaluate the subjective characteristics linked to the methodological process of its conduction. The analysis of the results allowed to verify that the use of the software Cmap Tools for the resolution of problems showed ample promising for the process of significant learning.